2019
DOI: 10.1016/j.hpb.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of bile leak testing in liver resection: a systematic review and meta-analysis

Abstract: Background: Bile leak following liver resection can be associated with significant morbidity. This systematic review and meta-analysis aims to evaluate the effect of intraoperative bile leak testing on postoperative bile leak rate and other complications after liver resection without biliary reconstruction for any cause. Methods: PubMed, MEDLINE, Embase, Cochrane Library and grey literature databases were searched for articles between 1960 and 2017 comparing bile leak rates with or without bile leak testing. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(98 reference statements)
0
4
0
1
Order By: Relevance
“…Among the liver morbidity, the more biliary collection tendency was observed initially in the laparoscopic group than open hepatectomy groups (5.9% vs. 0.6% vs. 2.9%, p = 0.098), and the difference with the hybrid group was significant after matching. Although the incidence was still low compared to 3.6–33% of previous studies 36 , the higher biliary collection in the laparoscopic group may be due to the pneumoperitoneum, which prevents the bile leak on the cut liver surface during liver parenchymal transection, making it difficult to find the bile leakage points, and the difficulty of controlling the bile leakage points with suture ligation 23 , 37 .…”
Section: Discussionmentioning
confidence: 90%
“…Among the liver morbidity, the more biliary collection tendency was observed initially in the laparoscopic group than open hepatectomy groups (5.9% vs. 0.6% vs. 2.9%, p = 0.098), and the difference with the hybrid group was significant after matching. Although the incidence was still low compared to 3.6–33% of previous studies 36 , the higher biliary collection in the laparoscopic group may be due to the pneumoperitoneum, which prevents the bile leak on the cut liver surface during liver parenchymal transection, making it difficult to find the bile leakage points, and the difficulty of controlling the bile leakage points with suture ligation 23 , 37 .…”
Section: Discussionmentioning
confidence: 90%
“…The results showed that the evidence is scanty and unconvincing. 9 Furthermore, the kind of surgical transection and surgical closure techniques have been evaluated. In the early 1970s the clamp-crushing technique as a novel technique for hepatic resections was introduced.…”
Section: Preliminary Datamentioning
confidence: 99%
“…A recent systematic review and meta-analysis on this topic studied the role of bile leak testing during liver resection including test substances like normal saline, methylene blue, fat emulsion, indocyanine green and air. The results showed that the evidence is scanty and unconvincing 9. Furthermore, the kind of surgical transection and surgical closure techniques have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Nghiên cứu của Yun (2017), đã cho rằng: Điều trị không mổ là chiến lược điều trị hiệu quả và xâm lấn tối thiểu đối với rò mật sau mổ, và lựa chọn phương pháp điều trị tuỳ thuộc từng loại rò mật; trong đó, nội soi mật tuỵ ngược dòng nên được xem là phương thức đầu tiên trong chẩn đoán và điều trị rò mật sau phẫu thuật gan mật [12]. Vaska và cộng sự (2019) đã kết luận: Kiểm tra rò mật thường quy trong mổ cắt gan làm giảm đáng kể tỷ lệ rò mật, thời gian nằm viện [13].…”
Section: Biến Chứng Rò Mật Và Tràn Dịch Màng Phổiunclassified